Histórias que se repetem: o abuso sexual incestuoso atravessando gerações - Paulino, Sandra Eloiza (2005)
The purpose of this study is to understand the family in which the intrafamily sexual abuse or incestuous abuse occurs, signalizing ways for the intervention in this kind of abuse that happens in different generations. As a way to approach to this subject, was used the author professional experience as social worker at PAVAS (Attention Program for Sexual Violence) at the Public Health School in USP (University of São Paulo). Starting with a survey of the medical registers from the cases that involved sexual abuse of children and teenagers of the female gender and hers respective fathers and stepfathers, the author focused the cases wherein also occurred sexual abuse in the previous generation, it means involving the mothers of the children and teenagers attended in the Program as victims themselves. After, was utilized a study of a particular case, being this case analyzed using the systemic theory, in order to understand the dynamic of a family in which the relations are involved by incest. The author began from the hypothesis that the incestuous relation experienced by the woman in her childhood created for her a reference and a model of family and this fact makes she unconsciously try to establish affective relations inside the patterns that was socially apprehended for her. That implies to reproduce the abusive patterns that was historically construct by the familiar relations and these can be transmitted as a legacy. The results point out to the complex familiar system, that is capable to determine rules to be followed by the members that constitute it, and for the necessity to create a intervention policy to attend the family in which the sexual incestuous occurs as a whole, and not only the components of this family isolated, avoiding by this way to characterize the persons in victims and executioners